Percepções das gestantes e fatores que influenciam a preferência da via de parto - SILVA, Erika Beatriz Borges (2019)
Pregnancy is considered a transition period and a complex experience with different aspects for each woman. Numerous physical and psychological changes take place during this period. Their experience at this time may leave indelible marks, positive or negative, for the rest of their lives. The choice of the way of delivery is a fundamental human right, however, the pregnant woman needs information and clarification about it. The possibility of being able to express their preference reflects on the autonomy of women. The objective of this study was to describe the factors that influence the choice of the birth route, of a qualitative nature, of the exploratory-descriptive type. The study was attended by 18 pregnant women enrolled and being followed up in the Prenatal Program, ranging in age from 20 to 39 years. The analysis of the data was made through the analysis of the content of the answers, from this analysis it was noticed that the route preferred by the pregnant women was normal, influenced by the recovery in the postpartum, which was very evident in the speech of the pregnant women. It was also observed that women were being informed about the risks and benefits of each birth route in the prenatal period, only in the last weeks of gestation, a fact that is worrying, since this information must be shared from the beginning of prenatal care. In addition, it is worth emphasizing the need to qualify prenatal care through health education actions, in order to provide pregnant women with the autonomy to make informed and informed choices.